Earnings Indicators under the Condition of Globalization - Siekelova Anna; Podhorska Ivana (SHS Web of Conferences, 2020)
The paper is focused on the analysis of the influence of partial indicators on the selected top indicator, which is the earnings. The profit is the resulting effect of the enterprise’s business activity and, at the same time, often the measure of whether the company is successful or not. Business performance data is one of the cornerstones for further corporate planning and decision making. It is necessary to point out the factors that influence the company’s result. The main purpose of the contribution is the pyramidal breakdown of the economic performance indicator to identify the main factors influencing its change over the two-year reference period. The pyramidal breakdown of the economic result is complemented by the breakdown of the ROE indicator.